Hypo-Expression of Tuberin Promotes Adenomyosis via the mTOR1-Autophagy Axis - Gu, Ni-Hao; Li, Guo-Jing; Yang, Bing-Xin; You, Min; Lin, Yu; Sun, Feng; Xu, Hong (Frontiers in Cell and Developmental Biology, 2021)
Adenomyosis (AM) is a disease in which endometrial tissue invades the myometrium and has a 10–60% prevalence in reproductive-aged women. TSC2 regulates autophagy via mTOR1 signalling in colorectal cancer and endometrial carcinoma. Dysregulation of autophagy is implicated in adenomyosis pathogenesis. However, whether TSC2 participates in adenomyosis via autophagy remains obscure. Here, we found that the expression of TSC2 in adenomyosis was significantly decreased than that in normal endometrium during the secretory phase. Moreover, TSC2 and autophagy marker expression was significantly lower in ectopic lesions than in eutopic samples. TSC2 downregulation inhibited autophagy through mTOR1 signalling pathway activation in endometrial cells, leading to excessive proliferation, migration, and EMT; TSC2 overexpression induced the opposite effects. Rapamycin treatment suppressed cell proliferation, migration and EMT in the absence of TSC2. In parallel, an autophagy-specific inhibitor (SAR-405) restored migration and EMT under rapamycin treatment in TSC2-knockdown Ishikawa cells. Finally, SAR-405 treatment promoted EMT and migration of overexpressing cells. Collectively, our results suggest that TSC2 controls endometrial epithelial cell migration and EMT by regulating mTOR1-autophagy axis activation and that hypo-expression of TSC2 in the endometrium might promote adenomyosis.